Pengaruh Persepsi Penilaian Prestasi Kerja terhadap Kepuasan Kerja Karyawan - Daniel Sylvester Simanjuntak; Kristanty Marina Natalia Nadapdap; Winarto Winarto (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2017)
The aim of this research is to examine the relationship between performance appraisal perception and job satisfaction. The research was conducted among an inspection, testing, certification, training and consultancy company in North Sumatera, where all the employees became the respondents. The research used a quantitative descriptive method by using a questionnaire, which has been filled out by 85 respondents. The results show that the performance appraisal perceptions affect the job satisfaction. Theoretical and practical implication will be discussed at the end of the paper .